Design of a star-like hyperbranched polymer having hydrophilic arms for anti-biofouling coating. Issue 7 (10th January 2019) - Totani, Masayasu; Liu, Ling; Matsuno, Hisao; Tanaka, Keiji
Abstract : A simple method for anti-biofouling coating based on a star-like hyperbranched polymer having hydrophilic arms. Abstract : A star-like hyperbranched polymer having hydrophilic poly(ethyleneoxide acrylate) arms (HB-PEO9A) was prepared by a core-first method based on atom transfer radical polymerization. The PEO9A layer coated on a solid substrate was dissolved by water, and effectively inhibited protein adsorption and cell adhesion.